2017
DOI: 10.1159/000478631
|View full text |Cite
|
Sign up to set email alerts
|

Correlating the Genetic and Physical Map of Barley Chromosome 3H Revealed Limitations of the FISH-Based Mapping of Nearby Single-Copy Probes Caused by the Dynamic Structure of Metaphase Chromosomes

Abstract: Genetic maps are based on the recombination frequency of molecular markers which often show different positions in comparison to the corresponding physical maps. To decipher the position and order of DNA sequences genetically mapped to terminal and interstitial regions of barley (Hordeum vulgare) chromosome 3H, fluorescence in situ hybridization (FISH) on mitotic metaphase chromosomes was performed with 16 genomic single-copy probes derived from fingerprinted BAC contigs. Long genetic distances at subterminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…For example, between the two adjacent markers InDel1 and InDel2, the ratio was 31.6 kb/cM, but the ratio was only 0.68 kb/cM between InDel2 and InDel3. This phenomenon was also observed in other plants, such as barley, where long genetic distances translated into short physical distances, and vice versa , and that was thought to be related to different frequencies of recombination events at different chromosome regions ( Bustamante et al, 2017 ). However, based on our results, it is hard to clarify whether there exists unequal distribution of recombination frequency along the linkage group, because the limitation of mapping population size and marker number used for map construction may influence the uniformity of marker distribution, thus affecting the ratio of physical to genetic distance.…”
Section: Discussionmentioning
confidence: 67%
“…For example, between the two adjacent markers InDel1 and InDel2, the ratio was 31.6 kb/cM, but the ratio was only 0.68 kb/cM between InDel2 and InDel3. This phenomenon was also observed in other plants, such as barley, where long genetic distances translated into short physical distances, and vice versa , and that was thought to be related to different frequencies of recombination events at different chromosome regions ( Bustamante et al, 2017 ). However, based on our results, it is hard to clarify whether there exists unequal distribution of recombination frequency along the linkage group, because the limitation of mapping population size and marker number used for map construction may influence the uniformity of marker distribution, thus affecting the ratio of physical to genetic distance.…”
Section: Discussionmentioning
confidence: 67%
“…Hasat root tips preparations using FISH analysis. Due to the large genome size of barley, researchers mostly prefer to use single-copy probes derived from BAC or YAC contigs (Vicient et al 1999, Acevedo-Garcia et al 2013, Bustamante et al 2017). In our study, we used direct PCR products derived from barley DNA to produce singlestranded probes were small, appx.…”
Section: Resultsmentioning
confidence: 99%
“…These anomalies were found to be due to the errors in genome assembly 32 . Furthermore, the evidence that genetic markers are often located at different physical position is highlighted by Bustamante et al 33 in barley. In this study, the authors investigated the positions and orders of genetically identified markers of chromosome 3H with a physical map, derived from fingerprinted BAC contigs.…”
Section: Discussionmentioning
confidence: 99%